A Ground Beetle, Calleida decora (Fabricius) (Insecta: Coleoptera: Carabidae) - D. L. Harris; W. H. Whitcomb (EDIS)
Calleida decora (Fabricius) is a small arboreal ground beetle, predaceous both as larva and adult. Common on various cultivated crops, it is apparently the only carabid to complete its larval development on Florida soybean foliage (Neal 1974). It is believed to be a major factor in suppression of several lepidopterous pests, e.g., velvetbean caterpillar, Anticarsia gemmatalis Hübner, on soybeans. This document is EENY-331 (originally published as DPI Entomology Circular 278), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2004.